Let's talk about being selfish - Berry, Joy Wilt.; Costanza, John (Chicago : Childrens Press, 1984)
Discusses the advantages of sharing, and the times when it is prudent to put something away rather than share it.
School Library Journal
3.2
K-3
Keywords: Sharing -- Juvenile literature; Sharing; Selfishness; Sharing